Participation of Latinos in the Diabetes Self-Management Program and Programa de Manejo Personal de la Diabetes. Issue 1 (18th March 2020) - Mendez-Luck, Carolyn A; Govier, Diana J; Luck, Jeff; Julyan, Esmeralda J; Mahakalanda, Shyama; Herrera-Venson, Angelica P
Abstract: Background and Objectives: The Diabetes Self-Management Program (DSMP) and Programa de Manejo Personal de la Diabetes (PMPD) have been shown to reduce complications from poorly controlled diabetes. Only a few research studies have examined Latino individuals' participation in them. This study examines workshop completion among DSMP and PMPD participants and the effects of race/ethnicity, workshop language, workshop type, and workshop site on program completion rates by participants. Research Design and Methods: We used data from the National Council on Aging's data repository of individuals who participated in DSMP or PMPD between January 2010 and March 2019. Using a pooled cross-sectional study design, we examined workshop completion among 8, 321 Latino and 23, 537 non-Latino white (NLW) participants. We utilized linear probability models to estimate the effects of race/ethnicity and workshop language/type among the full sample; a stratified model estimated the separate effects of workshop language, type, and delivery site among Latinos. Participant characteristics included age, sex, education, number of chronic health conditions, living arrangement, health insurance status, and geographic location of workshop. Results: Compared to NLW participants in DSMP English workshops, Latinos enrolled in any workshop had a higher probability of completing at least four workshop sessions, and Latinos enrolled in PMPD Spanish workshops had a higher probability of completing six of six sessions. Among the Latino subsample, participation in PMPD Spanish or English workshops was associated with completing at least four sessions or all six sessions compared with participation in DSMP Spanish or English workshops. Among Latino participants, the effects of workshop site on completion rates were mixed. Discussion and Implications: Diabetes self-management education programs tailored for Latino participants had higher completion rates. Further research is warranted to better understand the effect of workshop site and participant characteristics on completion of DSMP and PMPD programs.